Avaliação do serviço de atenção domiciliar de Pelotas - SAD HE/UFPEL: perfil epidemiológico e mapa de indicadores - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The objective of this study was to identify the epidemiological and clinical profile of hospitalized patients and analyze indicators. This is a descriptive and exploratory research, with a quantitative approach, carried out by collecting data from service monitoring spreadsheets. It was found that the profile of admitted patients is elderly users, predominantly women, coming from hospitals, with cancer as the most frequent underlying condition and palliative care as the reason for referral. There was a gradual increase in patient referrals, an adequate work capacity, and low home death rates. Systematic characterization of these profiles and indicators is essential for organizing work processes and planning future actions.
Evaluation of the home care service in Pelotas - SAD HE/UFPEL: epidemiological profile and map of indicators
Keywords: Epidemiology; Health indicators; Indicadores de saúde; Home care services; Serviços de assistência domiciliar; Epidemiologia; CNPQ::CIENCIAS DA SAUDE